The Jazz Patrol Community’s Strategy for Preserving Traditional Osing Songs in Banyuwangi - Fahmi Fahmi Dhiya'ul Auliya Milady (Repertoar, 2026)
This study aims to describe the musical style and strategies of the Jazz Patrol community in preserving traditional Osing songs in Banyuwangi. The Jazz Patrol community is a music group focused on preserving local culture through an innovative musical approach that combines traditional musical elements—such as patrol, angklung, and suling—with modern instruments like guitar, bass, and keyboard, all within the jazz genre. This approach serves as a cultural strategy that can reintroduce Osing-language songs to the younger generation. This study employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The results indicate that the Jazz Patrol’s musical style is collaborative and improvisational, while maintaining local character through the Osing language and the pentatonic scale characteristic of Banyuwangi. The strategies implemented by this community include planning creative programs, organizing performances, collaborating with national and international musicians, and using digital media for promotion and cultural education. Thus, Jazz Patrol not only serves as a platform for artistic expression but also acts as an agent of cultural preservation, adapting to changing times. This study is expected to serve as a reference for efforts to preserve other forms of traditional music in Indonesia.